Educação ambiental e comunidades rurais: as lutas entre a agricultura camponesa e o agronegócio no interior do estado do Maranhão - Protacio, Ana Paula Batista (2022)
In the present work, we chose Environmental Education and the rural communities of the State of Maranhão, the struggles and permanences in the rural territory. Our main objective was to analyze Environmental Education as a formal educational activity in rural communities in the interior of the state of Maranhão in the face of their challenges, struggles and permanence. Faced with the advance of agribusiness in the state since the 1970s, rural school education has faced several challenges and struggles for its emancipation, as its political project is antagonized to the agribusiness project, which is strongly present around schools, creating social conflicts, cultural, environmental and economic. Due to this situation, it is important to know and analyze the scenario, presenting the projects of the actors, verifying their nature and conflicts. It is hoped with this research, to subsidize with theoretical and practical elements on the current issue, in order to contribute to a permanent awareness by the different social groups in our society of the environment in which we live, understanding the need to ethically develop values and habits that provide a better quality of life and the guarantee of the right to life, through education and work, in a sustainable way. Also highlighting the inclusion of environmental education in basic education in Brazil, discussing the importance of content and its praxis in school spaces and in communication and learning with the surrounding community.